Humano e máquina: em busca de um duplo ciborgueano - Bertol, Evandro (2022)
This research in Visual Arts brings artistic achievements that address the anguish felt by the artist when interacting with the digital technological environment, aiming to explore the hybrid relations with the computer in digital art, using the selfie portrait as an artistic proposal. Conceptually, from this self-representation, the figure of the cyborg emerges, which serves as the guiding thread of the digital work. Knowing that, in art, it is not the computational machine that should prevail over the artist’s work, I try to take into account the subjectivity that exists in this action. This process of poetic research is supported by the method proposed by Sandra Rey (1996), based on René Passeron (1989), for practical and theoretical developments. The bibliographic support of Edmond Couchot (2003, 2017), Villém Flusser (1998) and Giorgio Agamben (2009) contributes to the understanding of technological interaction and use relationships; and Donna Haraway (2009) helps with the issues of the cyborg figure. I also count on David Le Breton (2013) for further clarification on the body impacted by technological means, along with Arlindo Machado (2001, 2002) in deepening the relationship between human and machine. As artistic references, the works of artists Stelarc, ORLAN, Lu Yang are relevant due to the technological interference in the physical and digital body, and Cindy Sherman with her portraits that contest the real appearance by unreal modification. After appropriating these references, I took selfies with a smartphone, followed by digital interference with the softwares Photoshop®, Illustrator® and CorelDRAW®. In the quest to identify the cyborg characteristics resulting from the amalgamation of the artist’s subjectivity with the scientific identity of machine programming, my portraits became cyborg doubles. Establishing the selfie as a self-portrait model, I carry out a dialogue with digital technology, through interferences carried out in the aesthetics of the images, seeking to highlight the proposed concept of the cyborg and projecting these relationships beyond those established between artist and machine, shifting the perception of the concept of cyborg to the regency of the power relations that comes from contact with technological means. The selfies presented are sources of questioning about my own image and the impact that technology has on the recognition of the created double; when promoting this movement of approximation between the human being and the machine, I perceive the desire to imbue it with humanity, while I am affected by the obsolescence of the body, in the face of the possible improvements offered by technology.